2017
DOI: 10.1007/s10517-017-3728-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of ATP-Sensitive K+ Channels in Myocardial Infarct Size-Limiting Effect of Chronic Continuous Normobaric Hypoxia

Abstract: The role of K channels in myocardial infarct size-limiting effect of chronic continuous normobaric hypoxia was examined in a rat model based on a 20-min coronary occlusion and subsequent 3-h reperfusion. Rats were adapted to normobaric hypoxia (12% O) for 21 days. This hypoxia produced a pronounced infarct size-limiting effect, which had been prevented by 0.3 mg/kg glibenclamide, a non-selective inhibitor of entire pool of K channels, or 5 mg/kg 5-hydroxydecanoate, an inhibitor of mitochondrial K channels. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…An important role of K ATP channels in the infarct-limiting and antiarrhythmic effects of CH was confirmed in other studies [ 40 , 200 201 ] . Studies showed that glibenclamide and 5-hydroxydecanoate, the two selective mitoK ATP channel inhibitors, eliminated the infarct-reducing effect of CCH (12% O 2 , 3 weeks) [ 42 , 202 ] , but the sarcK ATP channel blocker (HMR 1098) had no effect [ 42 ] . It should be noted that Forkel et al using glibenclamide could not confirm the involvement of K ATP channels in the increased tolerance of the RV to I/R in rats exposed to CH (10.5% O 2 , 2 weeks) [ 145 ] .…”
Section: The Mechanism Of the Myocardial Ischemic Tolerance Elicited ...mentioning
confidence: 99%
“…An important role of K ATP channels in the infarct-limiting and antiarrhythmic effects of CH was confirmed in other studies [ 40 , 200 201 ] . Studies showed that glibenclamide and 5-hydroxydecanoate, the two selective mitoK ATP channel inhibitors, eliminated the infarct-reducing effect of CCH (12% O 2 , 3 weeks) [ 42 , 202 ] , but the sarcK ATP channel blocker (HMR 1098) had no effect [ 42 ] . It should be noted that Forkel et al using glibenclamide could not confirm the involvement of K ATP channels in the increased tolerance of the RV to I/R in rats exposed to CH (10.5% O 2 , 2 weeks) [ 145 ] .…”
Section: The Mechanism Of the Myocardial Ischemic Tolerance Elicited ...mentioning
confidence: 99%